Effort-reward imbalance and quality of life of healthcare workers in military hospitals: a cross-sectional study - Tzeng Dong-Sheng; Chung Wei-Ching; Lin Chi-Hung; Yang Chun-Yuh (BMC, 2012)
Abstract Background Taiwan's National Defense Bureau has been merging its hospitals and adjusting hospital accreditation levels since the beginning of 2006. These changes have introduced many stressors to the healthcare workers in these hospitals. This study investigates the association between job stress, psychological morbidity and quality of life in healthcare workers in three military hospitals. Methods We posted surveys to 1269 healthcare workers in three military hospitals located in southern Taiwan. The surveys included the General Health Questionnaire (GHQ), the World Health Organization Quality of Life Questionnaire (WHOQOL-BREF), and the Effort-Reward Imbalance (ERI) Questionnaire. High effort-reward (ER) ratio and overcommitment were defined when scores fell into the upper tertile of the total distribution. Results The survey was completed by 791 healthcare workers. On average, women reported a higher ERI than men. High ERI was associated with younger age, higher psychological morbidity, and poor physical and psychological QOL domains in this population. High ER ratio and high overcommitment were associated with psychological morbidity and poor QOL in both sexes. However, high ER ratio was not significantly associated with the social QOL domain in either sexes or the physical QOL domain in males. Conclusions There was a clear association between ERI and QOL in the healthcare workers in the military hospitals under reorganization and accreditation in this study. We found ER ratio and overcommitment to be suitable indicators of job stress.